A butterfly shaped mobile biatrial cardiac mass: Myxoma or something else - Gupta, Pallav (Elsevier, 2014)
Primary cardiac tumors are rare with a reported prevalence of 0.01–0.02% based on pooled autopsy series. Although most mobile cardiac tumors arising from the interatrial septum and extending into the atria are thought to be benign myxomas, this may often not be true. Myxoid fibrosarcomas which in contrast to myxomas are malignant cardiac tumors often mimic the clinical and echocardiographic picture of atrial myxomas. We describe a rare entity of biatrial low-grade myxoid fibrosarcoma presenting in an adult patient as a butterfly shaped mass, with progressive shortness of breath and prolonged PR interval on the ECG that was pre-operatively thought to be a cardiac myxoma. The distinguishing echocardiographic features of the two entities are discussed.